2016
DOI: 10.1519/jsc.0000000000001368
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Agreement Between 4 Lactate Threshold Measurements Methods in Professional Soccer Players

Abstract: Cerda-Kohler, H, Burgos-Jara, C, Ramírez-Campillo, R, Valdés-Cerda, B, Báez, E, Zapata-Gómez, D, Cristóbal Andrade, D, and Izquierdo, M. Analysis of agreement between 4 lactate threshold measurements methods in professional soccer players. J Strength Cond Res 30(10): 2864-2870, 2016-Lactate threshold (LT) represents the inflection point of blood lactate values from rest to high-intensity exercise during an incremental test, is commonly used to determine exercise intensity, and is related to different positiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The T lac-log method, like the D max method, allows for T lac to be determined mathematically, and also does not rely on absolute concentrations of lactate. The T lac-log method, however, significantly under-predicted performance in the 5-km time trial; this finding has been observed in other research [ 16 , 18 ]. Although the T lac-log method is useful for fitting the data, there is very little research on whether T lac-log relates to performance [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 82%
“…The T lac-log method, like the D max method, allows for T lac to be determined mathematically, and also does not rely on absolute concentrations of lactate. The T lac-log method, however, significantly under-predicted performance in the 5-km time trial; this finding has been observed in other research [ 16 , 18 ]. Although the T lac-log method is useful for fitting the data, there is very little research on whether T lac-log relates to performance [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 82%
“…To quantify the agreement of the outcome measures between TM and RT, a Bland-Altman analysis was conducted. Priori defined 95% limits of agreement (LoA) of ±1km/h for IAT speed were considered to be of relevance [ 22 , 23 ]. The strength of the relationship between the primary outcome measures of the two running conditions was analyzed with the Pearson product-moment correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Incremental exercise tests are capable of providing input into aerobic endurance performance parameters (Joyner and Coyle, 2008; O’Brien et al, 2008; Faude et al, 2009; Midgley et al, 2009). In addition, heart rate and lactate thresholds are commonly used as a sensitive indicator of changes in training status in soccer players (Ziogas et al, 2011; de Lucas et al, 2014; Cerda-Kohler et al, 2016; Pallarés et al, 2016).…”
Section: Introductionmentioning
confidence: 99%